A new genus Viperinus Park with descriptions of two new species, and two new species of the genus Protolychnis Meyrick, 1925 (Lepidoptera, Gelechioidea, Lecithoceridae) in Kenya and Tanzania, with a checklist of the world species - Park, Kyu-Tek; Koo, Jun-Mo (Zootaxa, 2021)
A new genus Viperinus Park, gen. nov., belonging to Torodorinae (Lecithoceridae), is proposed, with descriptions of two new species, V. orbiosus Park & Koo sp. nov. from Kenya and V. pyknoistus Park & Koo, sp. nov. from Uganda. Furthermore, two new species of Protolychnis Meyrick, 1925, P. oculiella Park & Koo, sp. nov. and P. morogorensis Park & Koo, sp. nov., are described from Kenya and Tanzania, respectively. In addition, P. petiliella Park, 2020 is reported for the first time from Tanzania. The new genus, Viperinus is very similar to Protolychnis in the superficial characters, but it is separated from the latter by having unique characters in genitalia: a pair of processes arising from base of each valva in the male genitalia and a polygonal signal plate in the female genitalia. Images of adults and genitalia of the four new species are provided, and a checklist of Protolychnis Meyrick is also given.